1998
DOI: 10.1021/jp9804244
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Photophysical and Photochemical Properties of a Merocyanine Dye

Abstract: The photophysical and photochemical properties of the merocyanine dye 1-methyl-2-(4-hydroxystyryl)pyridinium betaine (M) have been studied in aqueous solution at the PM3-SCRF (SCRF = self-consistent reaction field) level of theory. The trans isomer is more stable than the cis one by 6 kcal/mol, and the energy gap decreases upon protonation to 2.4 kcal/mol. Protonation on nitrogen is energetically unfavorable and costs at least 31 kcal/mol more energy than protonation on oxygen. The acidity of the O-protonated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Suggested protolytic/photochemical cycle for MePM. [32] cle is shown in Figure 4. [32] Protonation of the trans isomer (I) produces H + trans (II), which undergoes light-induced isomerization to H + cis (III).…”
Section: Thermal or Photoisomerization Of Cis/trans Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested protolytic/photochemical cycle for MePM. [32] cle is shown in Figure 4. [32] Protonation of the trans isomer (I) produces H + trans (II), which undergoes light-induced isomerization to H + cis (III).…”
Section: Thermal or Photoisomerization Of Cis/trans Formsmentioning
confidence: 99%
“…[32] cle is shown in Figure 4. [32] Protonation of the trans isomer (I) produces H + trans (II), which undergoes light-induced isomerization to H + cis (III). This, after deprotonation, produces (IV), which after absorption of light is transformed back into (I); this step is irreversible.…”
Section: Thermal or Photoisomerization Of Cis/trans Formsmentioning
confidence: 99%
“…More recently, the electronic states of both cyanine and merocyanine dyes have been the subject of several MO SCF CI studies. 1,[16][17][18][45][46][47][48][49][50] In this section we focus our attention on the strongly allowed long-wavelength absorption which, for the three chromogen types, mainly arises from electronic excitation from the p H to the p* L orbitals. For the sake of brevity, we only report in Fig.…”
Section: Dependence Of the Colour Band Maximum (K Theo Max ) On The N...mentioning
confidence: 99%
“…a red shift of the visible absorption band as the solvent polarity decreases, this common feature of merocyanine derivatives being frequently attributed to a zwitterionic ground state. [9][10][11][12][13] However, contrary to this, Hamman and El-Nahas 15 have suggested that the hydrogen-bonding ability of the donor is a vital factor and Alberti and Echave 16 have reported nucleophile-carbonyl interactions (e.g. in acetone) and hydrogenbonding (e.g.…”
Section: Resultsmentioning
confidence: 97%